2002
DOI: 10.1088/0953-8984/14/8/323
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the magnetization distribution in Cr2O3using spherical neutron polarimetry

Abstract: The magnetization distribution due to the Cr3+ ion in Cr2O3 has been determined using spherical neutron polarimetry. The magnetic structure factors of h 0 l reflections have been measured out to sin θ/λ = 0.75 Å-1. The results show that the Cr3+ magnetic moment is reduced by the zero-point spin deviation and by covalent mixing to 2.48 µB. They are consistent with the Cr d electrons being in the trigonally symmetric a1 and e orbitals derived from the cubic orbitals with t2g symmetry. There is a small but si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
74
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 18 publications
10
74
2
Order By: Relevance
“…GGA+U indeed opens up a band gap and increases the Cr 3+ magnetic moment from ~2.5 µ B for GGA to ~2.9 µ B for GGA+U. Reduction from 3.0 µ B to 2.9 µ B is due to the covalency and comparison with the experimental value, 2.47 µ B , suggests that effect of quantum spin fluctuation is important in this system [16,17,18]. Note that in our electronic structure calculations, the principle axis is along the tetragonal axes which are not aligned with the cubic axis of the local crystal field of the CrO 6 system, which gives rise to the mixture of both t 2g and e g states in the former coordinate system for Cr 3d orbitals.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…GGA+U indeed opens up a band gap and increases the Cr 3+ magnetic moment from ~2.5 µ B for GGA to ~2.9 µ B for GGA+U. Reduction from 3.0 µ B to 2.9 µ B is due to the covalency and comparison with the experimental value, 2.47 µ B , suggests that effect of quantum spin fluctuation is important in this system [16,17,18]. Note that in our electronic structure calculations, the principle axis is along the tetragonal axes which are not aligned with the cubic axis of the local crystal field of the CrO 6 system, which gives rise to the mixture of both t 2g and e g states in the former coordinate system for Cr 3d orbitals.…”
mentioning
confidence: 61%
“…The magnetic signal disappears at the antiferromagnetic transition temperature T N ~ 93 K, consistent with the specific heat measurement. Note that the magnitude of the static magnetic moment (≈ 2.47 μ B /Cr) extracted from NPD measurement is smaller than the theoretical value of 3.0 μ B /Cr, which is attributed to quantum spin fluctuation (at low T) as well as due to the covalence [16,17,18].…”
mentioning
confidence: 64%
“…[3] after a purely magnetic FC in a positive H fc = 5 kOe. Analysis of the spin structures in Cr 2 O 3 using spherical neutron polarimetry [27][28][29] demonstrated that ME cooling in antiparallel E fc and H fc yields the AF domain type with the positive top magnetization, as shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 94%
“…, which crystallizes in the corundum structure (the space group is R3c) [28]. The formal configuration of the Cr-ions in Cr 2 O 3 is 3d 3 .…”
Section: Resultsmentioning
confidence: 99%